Highly chemoselective colorimetric/fluorometric dual-channel sensor with fast response and good reversibility for the selective and sensitive detection of Cu2+. Issue 30 (26th July 2019) - Guo, Zongrang; Niu, Qingfen; Li, Tianduo; Wang, Enhua
Abstract: A novel colorimetric and fluorometric dual-channel sensor DA with a favorable optical property and high specificity via a facile synthesis for Cu 2+ was developed. DA showed a remarkably rapid response and high selectivity for Cu 2+ over other metal ions with low detection limit of 15.1 nM. The sensing mechanism of DA for Cu 2+ was based on the chelation-enhanced fluorescence quenching (CHEQ) mechanism, and further confirmed by optical measurements, FTIR, HRMS and DFT calculations. Importantly, DA for sensing Cu 2+ possessed excellent sensing performances including colorimetric and fluorometric dual-mode detection, fast response, good reversibility, wide pH response range and strong anti-interference ability. Moreover, the DA could be not only applied to quantitatively detect Cu 2+ in environmental water, food and drink samples, but also show highly colorimetric detection of Cu 2+ on test strips and silica, indicating its possibility to be utilized as a convenient and low-cost sensor for environment and food monitoring. Graphical abstract: Image 1 Highlights: A new colorimetric and fluorometric sensor DA was synthesized. DA exhibits fast response and ultra sensitivity to Cu 2+ . DA is successfully used for tracking Cu 2+ in environmental water, food and drink samples. DA served as an efficient optical solid-state sensor for highly colorimetric detection of Cu 2+ on test strips and silica.